The technique of the six-tact crawl with the cross kicks - Sedlyar Y.V; Nosov A.I (Kharkov National Pedagogical University, 2012)
Variants of the six-tact crawl technique with the cross kicks are considered. Possibility of their use in sports swimming is defined. The specified variants on the basis of the analysis and synthesis of the data about the technique of the six-tact crawl with the cross kicks are developed. Possibility of their use in sports swimming in the course of self-training was defined. It has been specified that distinction between variants of the technique is defined by periods of the swimming cycle in which carry out the cross kicks. The training to these versions of the crawl technique is described. Variants which can be used in sports swimming and unsuitable for this purpose.